2017
DOI: 10.1105/tpc.16.00724
|View full text |Cite
|
Sign up to set email alerts
|

Maize NPF6 Proteins Are Homologs of Arabidopsis CHL1 That Are Selective for Both Nitrate and Chloride

Abstract: Nitrate uptake by plant cells requires both high- and low-affinity transport activities. nitrate transporter 1/peptide transporter family (NPF) 6.3 is a dual-affinity plasma membrane transport protein that has both high- and low-affinity functions. At-NPF6.3 imports and senses nitrate and is regulated by phosphorylation at Thr-101 (T101). A detailed functional analysis of two maize () homologs of At-NPF6.3 (Zm-NPF6.6 and Zm-NPF6.4) showed that Zm-NPF6.6 was a pH-dependent nonbiphasic high-affinity nitrate-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
107
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(130 citation statements)
references
References 67 publications
10
107
1
Order By: Relevance
“…Monocots and eudicots differ in the number of their NRT1.1 genes, with grass species typically having three to four NRT1.1 members and most eudicot species having only one NRT1.1 gene (Plett et al, 2010). Recently, Wen et al (2017) reported that two putative homologs of AtNRT1.1 (AtNPF6.3) in maize (Zea mays ssp mays), ZmNPF6.4 and ZmNPF6.6, display distinct substrates affinity for nitrate and chloride, indicating a possible functional divergence among different members of the NRT1.1 family in grasses. However, the biological functions and the possible divergence of the NRT1.1 genes in grass species remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Monocots and eudicots differ in the number of their NRT1.1 genes, with grass species typically having three to four NRT1.1 members and most eudicot species having only one NRT1.1 gene (Plett et al, 2010). Recently, Wen et al (2017) reported that two putative homologs of AtNRT1.1 (AtNPF6.3) in maize (Zea mays ssp mays), ZmNPF6.4 and ZmNPF6.6, display distinct substrates affinity for nitrate and chloride, indicating a possible functional divergence among different members of the NRT1.1 family in grasses. However, the biological functions and the possible divergence of the NRT1.1 genes in grass species remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis thaliana, the founding member of the NPF family, known as NPF6.3/NRT1.1/CHL1 (Tsay et al, 1993), is an exception because it has been demonstrated to behave as a dual affinity transporter (Liu et al, 1999) (Ho and Frommer, 2014). Later, this property has been demonstrated for NPF6 subfamily member in other species: in Medicago truncatula for MtNRT1.3/MtNPF6.8 (Morere-Le Paven et al, 2011) and in maize for ZmNPF6.6 (Wen et al, 2017). NPF6.3/NRT1.1/CHL1 switches between low-and high-affinity depending on the phosphorylation state of the threonine 101 (T101) that is monitored by the CIPK23 kinase and its regulating partner CBL9 (Liu and Tsay, 2003;Ho et al, 2009): the HATS mode is mediated by NPF6.3 transporters phosphorylated on T101.…”
mentioning
confidence: 85%
“…Lowering pH strongly increased the accumulation demonstrating a positive effect of H + on nitrate uptake. Since several anion transporters are able to transport nitrate as well as chloride, as ZmNPF6.4 and 6.6 (Wen et al, 2017), we then remove the chloride from the external solutions and replace it by gluconate. Nitrate accumulation in both conditions is very similar suggesting that chloride is not transported by NPF6.3 ( Fig.2B).…”
Section: Npf63/nrt11 a Low Affinity Nitrate Transportermentioning
confidence: 99%
“…Decades ago, active Cl − transporters such as Cl − /2H + symporters and passive Cl − influx/efflux channels in the plasma membrane of the root epidermis were identified using electrophysiological approaches [28], but to date, the corresponding candidate genes remain unknown. A previous study on Zea mays proposed that ZmNPF6.4 is likely a component of the plant root Cl − uptake system, as ZmNPF6.4 is a plasma membrane-localized, proton-coupled, chloride-selective transporter in root epidermal cells [29]. However, the transcriptional responses of NPF6.4 in plants to salt stress have not been investigated.…”
Section: The Possible Molecular Basis Underlying CL − Transport In Thmentioning
confidence: 99%